Synthesis, characterization and structural studies of sodium morpholine-4-Carbodithioate and its metal complexes - How, Fiona Ni Foong; Ahmad, J.; Abdul Halim, S. Nadiah (2015)
Sodium morpholine-4-carbodithioate and four metal complexes were synthesized and characterized using various physico-chemical techniques. The ligand behaved as a uninegatively charged bidentate ligands upon complexation with metal ions with the general formula of Ma(SS)2 and Mb(SS)3, where Ma is Cu(II) and Ni(II) and Mb is Co(III) and Fe(III). All the complexes have crystallographic data for structural comparison. Crystal structure of Iron and cobalt complexes existed in an octahedral coordination geometry with trapped lattice solvent. Nickel and copper complexes crystallized in square planar coordination geometry with no trapped solvent. The PXRD of all the complexes showed that the calculated PXRD data are coincide from the crystal structures of all the metal complexes.